Triangulating perspectives to inform the development of a smartphone application for foster, kinship, and adoptive parents. Issue 4 (2nd October 2019) - Forehand, Greg L.; Schisler-Blizzard, Allison D.; Deaver, Abigail Hemenway; Strolin-Goltzman, Jessica; Breslend, Nicole; Sullivan, Alexandra D. W.; Mendoza, Geovana S.; Bielawski-Branch, Amy; Jorgenson, Jennifer; Forehand, Rex
Abstract: This article describes the initial phase of a user-centered, inductive process for informing the development of a smartphone application (app) to complement an in-person trauma-focused knowledge and skills training class for child welfare resource parents (i.e. foster, kinship, and adoptive parents). Based on the participatory design approach for technology development, a qualitative study was designed to capture and triangulate relevant knowledge and opinions from resource parents, training instructors, and parenting education experts. The most prevalent themes emerging among these stakeholder groups included the need for a simple app interface and the potential for the app to (1) cultivate connection, affirmation, and combat resource parent feelings of isolation; (2) reinforce in-class knowledge and support skill practice at home; and (3) monitor resource parent, child, and family progress over time. Detailed findings are presented, including direct quotes from focus group and interview participants and elaboration on the prevalent themes, which may benefit others in the early stages of human services app design and contribute to the creation of guidelines for the development of technology-based human services interventions.